Design of Adenovirus 5 Vector with Adenovirus 26 Hexon Hypervariable Region Sequence using In Silico Approach - Afina Firdaus Syuaib; Ernawati Arifin Giri-Rachman; Aluicia Anita Artarini (Indonesian Society for microbiology, 2022)
Adenovirus type 5 (Ad5) is one of the vaccine vectors, including the COVID-19 vaccine. Pre-existing immunity to Ad5 may suppress the immunogenicity and efficacy of adenovirus vectored vaccine. The neutralizing antibodies are directed specifically toward seven hypervariable regions (HVR) of hexon proteins located on the outer surface of the capsid. This study aims to design an Ad5 vector that may circumvent anti-Ad5 immunity by designing a chimera Ad5 vector with the sequence of Ad26 HVR (Ad5HVR26) using in silico approach. Substitution of the Ad5 HVR DNA sequence may affect the alternative splicing process of adenovirus mRNA, which then influence the protein product. The splice site prediction of Ad5HVR26 chimera vector was found at HVR5, 6, and 7. The codon change in the splice site was performed to decrease the possibility of incorrect splicing, while retaining the original amino acid sequence. The HVR substitution in chimera vector Ad5HVR26 may also affect the interaction of hexon in the capsid. The HVR2 and HVR4 hexon proteins individually interact with other hexon proteins and IX protein. Thus, two designs of the Ad5HVR26 chimera vector were created in this research. The first design was the Ad5 chimera vector with complete substitution of HVR hexon by Ad26 sequence, with codon modification on the splice site. The second design was Ad5HVR26 chimera vector without the HVR2 and HVR4 substitution to maintain the hexon protein interaction with the capsid proteins. Production of the designed vectors are needed to prove the reduction of vector neutralization by pre-existing immunity.